Selected determinants of undertaking non-economic activities by companies (Economic and Political Thought, 2014)
Mainstream economics is based on the following assumptions: 1. Homoeconomicus is motivated by self-interest in economic activities; 2. The mainactors in the market are enterprises and households; 3. The main goal of anenterprise is always and only to maximize profit. Contemporary literatureindicates, however, that over time, these assumptions have been challenged.In addition, the neoclassical economics theory alleged that there seems tobe a lack of ethical and cultural aspects. The aim of this paper is to identifywhat determines setting objectives that go beyond profit maximization.Organizational culture, which largely depends on the owners and topmanagers, is a key determinant. M. Noga confirms that organizational cultureis an element that determines the growth and development of enterprises.This subject is important both from the scientific and practical point of view.We are witnessing in the economy that there is a shortage of knowledge aboutthe cultural context in managing and how to measure social welfare, which isinsufficiently taking into account the qualitative elements of socio-economicdevelopment. The study defines organizational culture as well as noneconomicactivities. Then dimensions of culture are characterized, especiallytaking into account the characteristics that contribute to undertaking noneconomicactivities. The paper contains the results of empirical research,which verify the theoretical assumptions and confirm the diversity of theobjectives set by contemporary enterprises.